Comparison of Popular Three-Dimensional Printing Materials for Oral and Maxillofacial Surgical Guidance Model - Adhitya, Mohammad; Sunarso, Sunarso; Muis, Abdul (Journal of Dentistry Indonesia, 2020)
The application of three-dimensional (3D) models in the medical field has become popular. However, the accuracy of 3D models for surgical guidance varies among different materials and 3D printing technologies, such as printing machine usage. Objectives: This study aims to obtain more information about the effect of three different materials printed using a fused deposition material printer from the same digital data source. This study also aims to compare, analyze, and test the materials’ ability. Methods: Each of the filament materials (acetylbutane stearate [ABS], polylactic acid [PLA], and high-impact polystyrene [HIPS]) are printed at two infill densities, their weight, volume, and dimension are measured, and infill materials are prepared. Printing time is estimated and calculated on the basis of printing properties by using Simplify3D© software. The strength and surface tension of each sample are examined via a drilling test. Results: PLA is better than ABS and HIPS for printing our 3D model because of its properties. Conclusion: Ideal 3D materials for printing 3D models should fulfill the criteria on accuracy, strength, weight, and durability for usage. However, production time and cost should also be considered.